2009
DOI: 10.1038/aja.2009.27
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the nitric oxide synthase gene and protein in corpus cavernosum by repeated dosing of udenafil in a rat model of chemical diabetogenesis

et al.

Abstract: Erectile dysfunction (ED) is a major complication of diabetes mellitus (DM). This study investigates the relationship between ED and the downregulation of constitutive nitric oxide synthase (cNOS) in the corpus cavernosum (CC) of diabetic rats. It also examines the effects of udenafil, a phosphodiesterase type 5 (PDE5) inhibitor, on ED and cNOS expression levels. After 16 weeks of daily oral treatment with udenafil in diabetic rats, the intracavernous pressure/mean arterial pressure (ICP/MAP) ratio was recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
0
13
1
2
Order By: Relevance
“…Decreased eNOS protein expression was reported both in STZ‐induced type 1 diabetic rats [52] and genetic type 2 diabetic rats [53], but some other studies reported no change [18,50,51]. Although previous studies reported that TNF‐α could significantly decrease eNOS expression by enhancing mRNA degradation [54], we found no significant changes in the total expression of eNOS in control or diabetic rats regardless of treatment in the current study.…”
Section: Discussioncontrasting
confidence: 74%
“…Decreased eNOS protein expression was reported both in STZ‐induced type 1 diabetic rats [52] and genetic type 2 diabetic rats [53], but some other studies reported no change [18,50,51]. Although previous studies reported that TNF‐α could significantly decrease eNOS expression by enhancing mRNA degradation [54], we found no significant changes in the total expression of eNOS in control or diabetic rats regardless of treatment in the current study.…”
Section: Discussioncontrasting
confidence: 74%
“…STZ-induced diabetic ED rats showed a decrease in the activity of NOS and the contents of NO as well as cGMP in the corpus cavernosum tissue, and thus was responsible for the impaired erectile function, consistently with the literature. [8][9][10] Administration of Yidiyin increased diabetic ED rats' erection numbers, enhanced NOS activity, and boosted the contents of NO and cGMP in the corpus cavernosum penis, and the indexes in the Yidiyin group were similar to that in the control group. In sum, increased NOS activity led to elevated NO levels, which resulted in increases in the content of cGMP, causing relaxation of the smooth muscle and triggering penile erection.…”
Section: Discussionmentioning
confidence: 67%
“…[36][37][38] Studies on corpus cavernosum tissue from type 1 and type 2 diabetic patients and animals have also disclosed low activity of NOS, diminished NO-mediated function, impaired GC, reduced cGMPgenerating capacity, and deficient PKG. [8][9][10]39) On the other hand, enhancing the activity of the NO-cGMP pathway by inhibiting PDE5, stimulating GC, or overexpressing PKG-1 improve the erectile function of patients and animals with diabetic ED. [40][41][42] According to reports, [43][44][45] some herbs, including Rehmannia glutinosa Steud., Epimedium brevicornum Maxim., and Cynomorium songaricum Rupr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of PDE5 enzyme might enhance nNOS enzyme activity and thereby augment neuronal NO synthesis and release. Earlier research showed that PDE5 enzyme interacts with nNOS and modulates nitrergic neurotransmission . Hence improvement in neurogenic relaxation might result from both increased NO release from nitrergic nerves and a direct action of sildenafil to prolong such CCSM relaxation.…”
Section: Discussionmentioning
confidence: 99%